Reptilian Innate Immunology and Ecoimmunology: What Do We Know and Where Are We Going?. (14th July 2022) - Field, Emily K; Hartzheim, Alyssa; Terry, Jennifer; Dawson, Grant; Haydt, Natalie; Neuman-Lee, Lorin A
Abstract: Reptiles, the only ectothermic amniotes, employ a wide variety of physiological adaptations to adjust to their environments but remain vastly understudied in the field of immunology and ecoimmunology in comparison to other vertebrate taxa. To address this knowledge gap, we assessed the current state of research on reptilian innate immunology by conducting an extensive literature search of peer-reviewed articles published across the four orders of Reptilia (Crocodilia, Testudines, Squamata, and Rhynchocephalia). Using our compiled dataset, we investigated common techniques, characterization of immune components, differences in findings and type of research among the four orders, and immune responses to ecological and life-history variables. We found that there are differences in the types of questions asked and approaches used for each of these reptilian orders. The different conceptual frameworks applied to each group has led to a lack of unified understanding of reptilian immunological strategies, which, in turn, have resulted in large conceptual gaps in the field of ecoimmunology as a whole. To apply ecoimmunological concepts and techniques most effectively to reptiles, we must combine traditional immunological studies with ecoimmunological studies to continue to identify, characterize, and describe the reptilian immune components and responses. This review highlights the advances and gaps that remain to help identify targeted and cohesive approaches for future research in reptilian ecoimmunological studies.